A decline in tuberculosis diagnosis, treatment initiation and success during the COVID-19 pandemic, using routine health data in Cape Town, South Africa. - Karen Jennings; Martina Lembani; Anneke C Hesseling; Nyameka Mbula; Erika Mohr-Holland; Vanessa Mudaly; Mariette Smith; Muhammad Osman; Sue-Ann Meehan (PLoS ONE)
Background Coronavirus disease (COVID-19) negatively impacted tuberculosis (TB) programs which were already struggling to meet End-TB targets globally. We aimed to quantify and compare diagnosis, treatment initiation, treatment success, and losses along this TB care cascade for drug-susceptible TB in Cape Town, South Africa, prior to and during COVID-19. Methods This observational study used routine TB data within two predefined cohorts: pre-COVID-19 (1 October 2018-30 September 2019) and during-COVID-19 (1 April 2020-31 March 2021). The numbers of people diagnosed, treated for TB and successfully treated were received from the Western Cape Provincial Health Data Centre. Pre and post treatment loss to follow up and cascade success rates (proportion of individuals diagnosed with an outcome of treatment success) were calculated and compared across cohorts, disaggregated by sex, age, HIV status, TB treatment history and mode of diagnosis. Results There were 27,481 and 19,800 individuals diagnosed with drug-susceptible TB in the pre- and during-COVID-19 cohorts respectively, a relative reduction of 28% (95% CI [27.4% - 28.5%]). Initial loss to follow up increased from 13.4% to 15.2% (p<0.001), while post treatment loss increased from 25.2% to 26.1% (p < 0.033). The overall cascade success rate dropped by 2.1%, from 64.8% to 62.7% (p< 0.001). Pre- and during-COVID-19 cascade success rates were negatively associated with living with HIV and having recurrent TB. Conclusions An already poorly performing TB program in Cape Town was negatively impacted by the COVID-19 pandemic. There was a substantial reduction in the number of individuals diagnosed with drug-susceptible. Increases in pre-and post-treatment losses resulted in a decline in TB cascade success rates. Strengthened implementation of TB recovery plans is vital, as health services now face an even greater gap between achievements and targets and will need to become more resilient to possible future public health disruptions.